; Eastern breadbasket obstructs its market and growth opportunities - Thomas Glauben; Maria Belyaeva; Ihtiyor Bobojonov; Ivan Djuric; Linde Götz; Heinrich Hockmann; Daniel Müller; Oleksandr Perekhozhuk; Martin Petrick; Sören Prehn; Alexander Prishchepov; Swetlana Renner; et al. (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
, , , , . , , , . , . – – Because of its enormous land and yield potentials, the breadbasket of the East, i.e. Russia, Ukraine and Kazakhstan are increasingly important for world grain markets. However, counterproductive market and trade policies, continual farm-level productivity gaps and deficits in marketing infrastructure consistently obstruct the breadbasket's production and market potentials. A prerequisite for their realization would be prioritizing market-conforming and export-oriented policies, as well as massive investments into spatial and farming infrastructures.
urn:nbn:de:gbv:3:2-54807
Keywords: 330